A case of acute abdomen caused by spontaneous rupture of a splenic abscess secondary to cancer of the splenic flexure - Pavlidis, Efstathios T (J Surg Case Rep, 2021)
Splenic abscesses are rare, difficult to diagnose, difficult to treat and usually appear in immunosuppressed patients. We present the case of a 64-year-old patient with left pleuritic chest pain, anorexia and fever with rigors diagnosed with splenic abscess due to splenic flexure colon cancer. The abscess spontaneously ruptured and the patient was operated on for acute abdomen. Splenectomy and Hartmann’s hemicolectomy were performed. The patient was discharged from the hospital and referred to the oncologic department. Continuous spread of infection and especially initiating from a cancer lesion is a usual mechanism of splenic abscess formation. Although computed tomography-guided percutaneous drainage is the treatment of choice, an exploratory laparotomy was necessary in this case because of the rupture of the abscess. It is important for the clinicians to include splenic abscesses and their complications in the differential diagnosis of acute abdomen.